2017
DOI: 10.5433/1679-0359.2017v38n4p2051
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile and lambs’ meat quality fed with different levels of crude glycerin replacing corn

Abstract: This study aimed to evaluate the Texel lambs' meat quality fed with increasing levels of crude glycerin (0, 7, 14, and 21% of dry matter) in the diet. Thirthy-two-two non-castrated male Texel lambs were used, with initial weight of 15.9 ± 4.1 kg, using a completely randomized design with four treatments and eight repetitions, per treatment. Upon reaching the average weight of 35 kg, the animals were slaughtered. The meat chemical composition was similar among treatments (P>0.05) and total lipids and crude prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
2
0
1
Order By: Relevance
“…These results also match the findings of Gomes et al (2012) and Fidelis et al (2017), who reported a similar pH in Nellore livestock, 24 h after they were slaughtered. Almeida et al (2017) mentioned that the pH recommended for a good quality meat in small ruminants must fluctuate between 5.5 and 5.8; a similar value was recorded in this study for the feed with 10 and 16% CP for the 5.5 and 5.8 pH, respectively.…”
Section: Resultssupporting
confidence: 85%
“…These results also match the findings of Gomes et al (2012) and Fidelis et al (2017), who reported a similar pH in Nellore livestock, 24 h after they were slaughtered. Almeida et al (2017) mentioned that the pH recommended for a good quality meat in small ruminants must fluctuate between 5.5 and 5.8; a similar value was recorded in this study for the feed with 10 and 16% CP for the 5.5 and 5.8 pH, respectively.…”
Section: Resultssupporting
confidence: 85%
“…The pH found is consistent with several researches with the Texel breed in confinement, with lambs slaughtered between 30 and 45 kg, with variations between 5.4 to 5.8 (Lima et al, 2013;Rego et al, 2017;Rego et al, 2019); and the meat protein values are in accordance to Texel lambs slaughtered with an average of 35 kg (Rego et al, 2017;Rego et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Datas from three differents articles, with texel lamb breed, slaughtered before 6 months of age and feeded with highest concentrate diet (more than 60%), with the analysis did in the same machine, has variation for shear force in 3.1 to 7.9 kgf/cm² (Lima et al, 2013;Rego et al, 2019;Rego et al, 2017) For sheep meat, color values are reported as L* 31.36 to 38.0, for a* 12.27 to 18.01 and for b* 3.34 to 5.65 (Bressan et al, 2001). In this study, meat average values of L* (39.11), a* (18.75) and b* (13.76) higher than the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Meat from very lean animals has less intense flavor because the amount of intramuscular fat can directly affect the sensory properties of the meat, producing detectable changes in palatability. This sensory difference, especially in relation to the meat flavor, can be explained by the animals diets, and reflects the differentiated production of volatile fatty acids by rumen microorganisms that in turn alter fat deposition in the muscle tissue (Santos et al, 2013;Rego et al, 2017). The amount of intramuscular fat can affect the sensory properties of the meat by replacing the muscle fiber with fat, producing detectable changes in the palatability of the animals that received food ad libitum.…”
Section: Treatmentsmentioning
confidence: 99%